Flashpoint and Flame Spread Analysis of Material Coconut Fiber (Cocus Nucifera) Using Chemical Treatment of Alkali NaOH as a Sound Absorber Material in Ship - Alam Baheramsyah; Ede Mehta Wardhana; Nasa dityas Fariz Pradani (International Journal of Marine Engineering Innovation and Research, 2021)
The use of sound absorbers on many ships made from glass wool. Glass wool has a negative impact on health, which can irritate the skin and disrupt the respiratory system. Therefore, it is necessary to have an alternative sound insulation material that is eco-friendly which has capabilities comparable to glass wool, and can also be used as heat insulation on ships. These alternative ingredients are materials from natural fiber. This research made sound absorbers using coconut fiber by soaking fiber into an alkali NaOH solution. Materials are selected based on density, economic value, and ease in the manufacturing process. The sound absorbers are modified using coconut fiber which is given a soaking treatment of alkaline NaOH solution and distilled water with a percentage of 15%. Soaking aims to remove lignin content and improve the mechanical properties of coconut fiber. In this research, 9 variations were made with different compositions. Tests are based on ASTM E84 to determine the flashpoint value and the safe flame spread on the ship. From the test results, it was found that coconut coir material was given a soaking treatment of alkaline NaOH solution with a percentage of 15% for 2 hours with a density of 0.3 gr/cm3 and thickness 30 mm and using a polyurethane adhesive. The time to reach the flashpoint is 20.45 seconds and the average temperature of flame spread is low when compared to other specimens including glass wool. The conclusion obtained is that the sound absorbers are safe when used on a ship.